Interacción entre gametos : ¿Cómo lo logra el espermatozoide? (2000)
ABSTRACT: The interaction between sperm and oocyte preceded by a series of events in the sperm known as "capacitation"; these changes include a dramatic increase in mobility, a rise in intracellular Cat` concentration and destabilization of the spermatic membrane. As a result of these changes, the sperm acquires the ability to contact the pellucid zone of the egg, to undergo acrosomic reaction, to pass through the periviteline space and to carry out the interaction between the spermatic head and the plasmatic membrane of the oocyte. This process leads in turn to events called "activation of the oocyte", which make possible both the conclusion of meiosis II and initiation of the cellular mitotic cycle. Two hypotheses exist to explain the activation of the oocyte induced by the sperm. The first is the hypothesis of the "receptor", where the fertilizing sperm would interact with a specific surface receptor on the oocyte, this interaction would allow the transmission of signals and later activation. The other hypothesis is that of lusion", which argues for the existence of a spermatic cytosolic factor that occurs after the fusion between membranes of the oocyte and the sperm. According to this second hypothesis, the sperm enters to the oocyte cytoplasm and activates the pathways that make oocyte activation possible.